ANALISIS KEAUSAN SHAFT PADA FRONT IDLER EXCAVATOR (BACKHOE) HITACHI TIPE EX-100 - Widodo, Kurniawan Rahmat (Jurnal Konversi Energi dan Manufaktur, 2022)
Backhoe is one type of excavator that is widely used in agricultural and construction applications as digging, lifting, and loading equipment. The sandy and rocky backhoe work location will accelerate wear on the undercarriage components, especially on the front idler component, namely the shaft. The existing data shaft is always damaged with a usage time of less than a year. For this reason, the author is interested in analyzing shaft wear on the Hitachi front idler backhoe type Ex-100 which often occurs at the Highways Service of Kudus Regency, so that in the future damage to this track system can be minimized. Several stages were carried out in this study, including observing how the operator works and the work location of the backhoe, observing the damage that occurs to the front idler component, measuring the initial dimensions and dimensions after wear on the front idler component, namely the idler, shaft, and bushing, testing the hardness of the material. front idler component in POLINES, and data processing and analysis of the causes of damage. The front idler shaft suffers from abrasive wear which can be seen from the visible scratches at the wear site on the shaft. The maximum stress that occurs in the contact area is 2.05 kN/mm2. Shafts should have a lifetime of more than 6 years but the shaft wears 13 mm in less than 1 year. This is due to external factors, namely sand and rocks that accelerate the occurrence of abrasion on the shaft.